HUBUNGAN SELF-EFFICACY DENGAN TINGKAT STRES PADA MAHASISWA YANG MENYUSUN TUGAS AKHIR - Fatimah Zahra; Retno Yuli Hastuti; Nur Wulan Agustina; Arlina Dhian Sulistyowati (Universitas Muhammadiyah Klaten, 2025)
Students have a final project as a graduation assignment from college. In preparing the final project, students generally experience difficulties including determining the title, finding references, difficulty collecting data, obstructed guidance schedules, many revisions, lack of rest and difficulty concentrating. This can trigger negative feelings that make students prejudice negatively so that the loss of self-confidence called self-efficacy triggers stress. Students must be able to manage their self-efficacy to help them deal with a variety of situations. This study aims to determine the relationship between self-efficacy and stress levels in students who prepare final assignments. This type of research is quantitative correlation with a cross-sectional approach. The population of this study was students who compiled the final project at Universitas Muhammadiyah Klaten with stratified random sampling technique. The instruments used were DASS and Self-efficacy Questionnaire. The results showed that out of 146 respondents most of the respondents were at a moderate level of self-efficacy with stress levels mostly in the mild range. Spearman rank test analysis results significant value (p) value 0.000 (α=0.05). The results of this study indicate a significant relationship and the correlation level of this study is in the strong category with the direction of the correlation. The correlation level of this study is in the strong category with a positive relationship direction..